2021
DOI: 10.1108/efcc-12-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Ecology mechanism of female talents social mobility

Abstract: Purpose With the development of social economy, the problem of female labor force and talent ecology mechanism has become increasingly prominent. They do not assign jobs according to their abilities, but decide their duties according to their interpersonal relationships. The uneven distribution of human resources makes the difference, the impact of the female talent social mobility tends to solidify and the social strata between the contradictions are deepening. Design/methodology/approach This paper mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“… 89 , 90 For example, an analysis revealed that mindfulness is negatively linked to negative feelings and positively connected to psychological health in survivors of cancer as it empowers them to suspend judgment and accept their current conditions. 91 , 92 …”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“… 89 , 90 For example, an analysis revealed that mindfulness is negatively linked to negative feelings and positively connected to psychological health in survivors of cancer as it empowers them to suspend judgment and accept their current conditions. 91 , 92 …”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%